Tool-supported building of DSLs from OWL ontologies - Ceh, Ines (2011)
Domain-specific languages (DSLs) are computer languages intended for problem solving in a specific domain. Ontology is a formal representation of a set of concepts from a particular domain and the relations between them. An ontology may be used to describe a domain and to reason about the entities within the domain. This paper presents an Ontology2DSL framework to build DSLs from OWL ontologies. Ontology2DSL enables the semi-automated construction of a formal grammar and programs from an OWL ontology. The design approach, the functionalities of the framework, and a case study are also addressed in this paper. Special attention is paid to the architecture that encompasses the following components: the transformation pattern builder, the OWL parser, the rule reader, the rule execution component and the transaction logger.